Cognitive Load and Occupational Injuries - Eric Bonsang; Eve Caroli (Institute of Labor Economics (IZA), 2021)
We investigate the relationship between cognitive load and occupational injuries. Cognitive load is defined in the literature as a tax on bandwidth which reduces cognitive resources. We proxy cognitive load with the number of non-professional tasks that individuals perform during weekdays. The underlying assumption is that when individuals perform many of those tasks, this requires mental organization which reduces available cognitive resources. We show that being cognitively loaded is associated with an increase in the risk of occupational injury for both males and females. The effect is stronger for individuals in high-risk occupations and, among those, for low-educated workers.
Keywords: J28; J81; D91; 330; work injury; cognitive load; time-use data